Analysis Of The Factors That Cause To Learning Difficulties Among Elementary School Students In The Digital Era - Siti Rohmah; Dessy Putri Wahyuningtyas; Nanda Saputra; Agus Nugroho; Trimey Liria Hutauruk (Cendikia : Media Jurnal Ilmiah Pendidikan, 2022)
The digital era in education is characterized by the development of ICT technology that is integrated into the learning process and school-based learning activities. Almost all schools currently implement ICT-based instruction in every academic area. In the digital age, the roles of professors and students have evolved. Teachers become partners and collaborators between subjects and technology, but students become information recipients who must be able to comprehend and investigate knowledge based on student-centered learning. In addition to a lack of understanding of digital literacy, which results in an inability to comprehend learning, there are undoubtedly student issues in the learning process. This research intends to perform a comparative literature review to determine the causes of elementary school pupils' learning challenges. The results of the study explain that a summary of the study literature demonstrates that in order to understand the causes of student learning difficulties in elementary school, it is necessary to understand the characteristics of the causes of student learning difficulties and the internal and external factors of students, so that strategies can be devised to overcome student difficulties. Of course, teachers and schools play a crucial role in overcoming student difficulties. reducing and aiding students in overcoming their restrictions and inability to comprehend each learning topic. Changes in the learning process that are effective and innovative with the aid of technology will undoubtedly make the learning environment enjoyable so that students are able to comprehend the lessons taught.